MORPHOLOGICAL STRUCTURE AND SOURCE MODELS IN UZBEK TERMINOLOGY (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The topic “Morphological Structure and Source Models in Uzbek Terminology” focuses on the linguistic mechanisms and models through which Uzbek scientific and technical terms are formed and systematized. It examines the morphological patterns of term creation, including affixation, compounding, reduplication, and abbreviation, which play a central role in expanding the terminological system of the Uzbek language. The study also explores source models such as native Uzbek formations, borrowed models from Arabic, Persian, Russian, and English, as well as international terminological elements. Special attention is given to the interaction between native and borrowed morphemes in the formation of hybrid terms and to the adaptation of foreign models into the morphological system of Uzbek. The research highlights the significance of morphological productivity and structural regularity in ensuring the transparency, precision, and standardization of Uzbek terminology in various scientific fields.